2017
DOI: 10.1186/s12864-017-3996-8
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome profiling reveals translational regulation of mammalian cells in response to hypoxic stress

Abstract: BackgroundRetinal pigment epithelium (RPE) cells transfer oxygen and nutrients from choroid to the neural retina. Reduced oxygen to RPE perturbs development and functions of blood vessels in retina. Previous efforts of genome-wide studies have been largely focused on transcriptional changes of cells in response to hypoxia. Recently developed ribosome profiling provides an opportunity to study genome-wide translational changes. To gain systemic insights into the transcriptional and translational regulation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 58 publications
3
19
2
Order By: Relevance
“…The main ORFs whose translation was hindered by 5 0 UTR cryptic proteins mainly regulate transcription, translation, and antiviral responses (Figure 6E). Translation of 5 0 UTRs is known to negatively regulate translation of downstream ORF in cell stress (Jiang et al, 2017;Reverendo et al, 2019;Young and Wek, 2016). Our findings suggest that this extends to cryptic proteins.…”
Section: Discussionmentioning
confidence: 52%
“…The main ORFs whose translation was hindered by 5 0 UTR cryptic proteins mainly regulate transcription, translation, and antiviral responses (Figure 6E). Translation of 5 0 UTRs is known to negatively regulate translation of downstream ORF in cell stress (Jiang et al, 2017;Reverendo et al, 2019;Young and Wek, 2016). Our findings suggest that this extends to cryptic proteins.…”
Section: Discussionmentioning
confidence: 52%
“…A major focus of study of these translation-regulating pathways has been the analysis of downstream effects. Global analyses identifying and quantifying the specific translational output of translation regulation by eIF2a and mTOR have largely been carried out by ribosome profiling (Hsieh et al, 2012;Jiang et al, 2017;Reid et al, 2014;Sidrauski et al, 2015;Thoreen et al, 2012). These studies revealed a low number of differentially translated transcripts, despite showing extensive global downregulation of translation.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia alters genome-wide gene expression at both the transcription and translation levels. Ribosome density at the 5′-UTR significantly increases under hypoxic conditions and is positively correlated with the presence of upstream open reading frames in the 5′-UTR of mRNAs [ 30 ]. Interestingly, in a study of native Tibetans residing at different HAs, the rs6756667 A allele was dominant.…”
Section: Discussionmentioning
confidence: 99%